The USA and Southern Rhodesia, 1953-1969 - Boxer, AKA (2013)
Existing studies of this topic have not made enough use of the British archives. Nor have they analysed the American domestic response to UDI in sufficient depth. The policies of successive American administrations as regards the Rhodesian problem can only be fully understood as part of Washington’s attitude to Britain, to Africa in general, and to southern Africa in particular. And, because the issue of white minority rule in Africa raised powerful emotions both in the African American community and among white opponents of civil rights, the Rhodesian crisis became a part of the politics of racial equality within the USA, playing a key role in the developing ideologies of these two communities. This thesis is based on research in both American and British archives and aims to show that the prevailing interpretation, especially of the policies of the Johnson Administration once Rhodesia had made its illegal declaration of independence in November 1965, is mistaken. Scholars have tended to take at face value the oft-repeated claim of US policy-makers that Rhodesia was a British problem, that they wished to be no more than helpful bystanders, supporting British efforts to see the downfall of the illegal regime and the creation of a government based on majority rule, and that when they did intervene, it was merely to urge the British to be firmer in their resolve to end the rebellion. The central contention of this thesis is that the officials shaping African policy in the Johnson Administration were intimately involved in the management of the crisis and that, far from resisting a solution that legitimised the white minority regime, they actively encouraged the British to settle with the illegal government.